2022
DOI: 10.3389/fpsyt.2022.925830
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Young Clients' Communications About Their Suicidality on a Text Message Helpline: “I'm Scared of What I Might Do to Myself”

Abstract: BackgroundYouth suicide is a major international concern and prevention is a priority. In most cases suicidal behavior would be preceded by a period of suicidal ideation. Although feeling suicidal is recognized as a risk factor for suicide, there is little research which captures young people's own experience of suicidality in a moment of crisis.AimsThis study aimed to explore young people's own accounts of their suicidality in the moment in which they experienced it.MethodThis qualitative study examined clien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…This re-sult is a significant finding in the context of suicide prevention in the context of climate change and associated mental health burden. The results of this study are consistent with previous research on technology-enhanced suicide prevention interventions, which have shown significant reductions in the prevalence and intensity of suicidal ideation [56,57]. This reduction in intensity aligns with the assertion that suicidal ideation must become an essential intervention target [58].…”
Section: Discussionsupporting
confidence: 90%
“…This re-sult is a significant finding in the context of suicide prevention in the context of climate change and associated mental health burden. The results of this study are consistent with previous research on technology-enhanced suicide prevention interventions, which have shown significant reductions in the prevalence and intensity of suicidal ideation [56,57]. This reduction in intensity aligns with the assertion that suicidal ideation must become an essential intervention target [58].…”
Section: Discussionsupporting
confidence: 90%